Effect of Body Size on Methylmercury Concentrations in Shoreline Spiders: Implications for Their Use as Sentinels. (10th March 2021) - Hannappel, Madeline P.; Chumchal, Matthew M.; Drenner, Ray W.; Kennedy, James H.; Barst, Benjamin D.; Castellini, J. Margaret; Nolan, Audrey R.; Willoughby, F. Manton; Trauffler, Lexton P.
Abstract: Shoreline spiders have been proposed as sentinels to monitor aquatic contaminants including methylmercury (MeHg). The present study examined the effect of spider body size on MeHg concentrations in shoreline spiders. We collected 6 taxa of spiders belonging to 4 families (orb‐weavers [Araneidae], long‐jawed orb weavers [Tetragnathidae: Tetragnatha sp.], jumping spiders [Salticidae], and wolf spiders [Lycosidae: Pardosa sp., Rabidosa sp., and Schizocosa sp.]) from the shorelines of 14 human‐made ponds at the Lyndon B. Johnson National Grasslands in north Texas (USA). As a proxy for body size, we measured leg length (tibia + patella) of each spider. Spider taxa differed by 3‐fold in mean MeHg concentration, and MeHg concentrations in 4 of 6 spider taxa increased significantly with leg length. The present study is the first to demonstrate that shoreline spider MeHg concentrations increase as a function of spider body size. Because spider size may account for some within‐taxa variation in MeHg concentrations, future studies that utilize spiders as sentinels of aquatic contamination by MeHg or other biomagnifying contaminants should take spider size into account. Environ Toxicol Chem 2021;40:1149–1154. © 2020 SETAC. Abstract : In the present study, we demonstrate that concentrations of methylmercury (MeHg) increase as a function of spider body size.